Analgesic, Antioxidant, Anti-Inflammatory, and Wound-Treating Actions of Bitter Apricot Kernel Extract - Mohamed Amine El-Hajjaji; Kawtar Fikri-Benbrahim; Najoua Soulo; Ghizlane Nouioura; Hassan Laaroussi; Pedro Ferreira-Santos; Badiaa Lyoussi; Zineb Benziane Ouaritini (Hindawi Limited, 2024)
Apricot (Prunus armeniaca L.) kernels have been widely employed in phytomedicine for treating different ailments. This study aims to unveil the phytochemical composition by HPLC-ESI-MS, in vitro antioxidant activity, and examine certain pharmacological effects of the hydro-ethanolic extract from bitter apricot kernels (BAK). Obtained results indicated that the BAK extract presents a content of 4.58 ± 0.15 mg GAE/g extract of TPA and 1.68 ± 0.09 mg QUE/g extract of TFA, respectively. HPLC-ESI-MS analysis discovered the presence of 17 phenolic compounds including phenolic acids and flavonoids like 3,4-dihydroxybenzoic acid, gallic acid, caffeic acid, (+)-catechin, epicatechin, and others, with associated antioxidant power. Regarding the studied potential pharmacological effects, notable analgesic activity at a dosage of 100 mg/kg BW was recorded with 63.46% protection. In the anti-inflammatory test, significant inhibition was observed after 6 hours of treatment (77.4%) compared to untreated animals. Moreover, the daily application of ointment formulated with 10% BAK extract resulted in a remarkable healing of wounds and burns in rats. These findings underscore the increasing evidence supporting the potential use of apricot kernel extracts in treating various diseases.